2020
DOI: 10.1186/s13756-020-00760-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of animal health and drug use practices in India, and their possible link to antimicrobial resistance

Abstract: Background: Livestock production, particularly the dairy sector, is important for food and nutritional wellbeing of communities in India, it supports livelihoods of many farmers, and contributes to the economy of the country. India is a high consumer of antibiotics and antimicrobial resistant (AMR) bacteria are a major public health concern. Objectives: Our objectives were to identify animal health and drug use practices that may contribute to emergence and spread of AMR in the country, review previous AMR-mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 72 publications
4
52
0
1
Order By: Relevance
“…There are limited studies from India on antibiotic usage patterns for various conditions in animal husbandry [ 12 ]. The present study listed major disease conditions of bovines requiring antibiotic usage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited studies from India on antibiotic usage patterns for various conditions in animal husbandry [ 12 ]. The present study listed major disease conditions of bovines requiring antibiotic usage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 98.7% veterinarians believed that antibiotic resistance was a serious public health issue, in similar line with the previous studies [ 35 , 36 ]. In addition, earlier studies also have reported a large number of untrained personnel (quacks) in veterinary practice in India, which might be due to unaffordable professional veterinary services for marginalized farmers [ 12 , 30 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it occurs at a time when the human and veterinary pharmaceutical industry, farmers, and researchers seek solutions to the serious issue of antimicrobial resistance (Collignon & McEwen, 2019;Iannino et al, 2019). The reasons for this cooperation are the rapid expansion of resistance associated with the globalization of trade, a decrease in therapeutic options to combat it, an increase in productive-reproductive losses because of high morbidity and mortality, and the possibility of transferring resistant microorganisms of animal origin to humans (Astorga et al, 2019;Feiyang et al, 2019;Mutua et al, 2020;Van Boeckel et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is considerable interest in herbal products despite the availability of multiple synthetic chemicals intended for veterinary use (Martínez & Jiménez, 2017). Several factors explain this, including the search for alternative, effective, and economical solutions to unresolved global health problems such as microbial resistance; the promotion of rural development along with its biocultural heritage (Aziz et al, 2018a;Mutua et al, 2020;Suroowan et al, 2017); and the similarities between veterinary and human ethnomedicine (Miara et al, 2019). Regardless of the reasons, the use of plant-based veterinary products as a therapeutic complement, or even as the only available option, has recently acquired tremendous importance in terms of animal welfare (Feyera et al, 2017;Lans, 2019;Sharma & Manhas, 2015;Yigezu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%